2019
DOI: 10.1021/acs.jafc.9b02951
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Apoptosis of Gaeumannomyces graminis (Get) Induced by Carabrone

Abstract: Carabrone is isolated from Carpesium macrocephalum Franch. et Sav, which has good fungicidal activity, especially for Gaeumannomyces graminis (Get). According to previous studies, we speculated that carabrone targets the mitochondrial enzyme complex III of Get. To elucidate the mode of action, we used carabrone to induce oxidative stress and apoptosis in Get. Incubation with carabrone reduced the burst of reactive oxygen species (ROS) and mitochondrial membrane potential, as well as phosphatidylserine release.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Moreover, the designed compounds could strongly induce the generation of late apoptotic cells, with the proportion changing from 0.1 to 43.7% for Xoo cells and from 0.9 to 34.4% for Xac cells. The reactive oxygen species (ROS) in tested pathogens must be monitored using the ROS detection kit because excessive ROS is a key marker that can activate an apoptotic response . Notably, the amount of ROS in pathogens triggered by THC compounds gradually increased with the elevation of drug dosages (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the designed compounds could strongly induce the generation of late apoptotic cells, with the proportion changing from 0.1 to 43.7% for Xoo cells and from 0.9 to 34.4% for Xac cells. The reactive oxygen species (ROS) in tested pathogens must be monitored using the ROS detection kit because excessive ROS is a key marker that can activate an apoptotic response . Notably, the amount of ROS in pathogens triggered by THC compounds gradually increased with the elevation of drug dosages (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The reactive oxygen species (ROS) in tested pathogens must be monitored using the ROS detection kit because excessive ROS is a key marker that can activate an apoptotic response. 54 Notably, the amount of ROS in pathogens triggered by THC compounds gradually increased with the elevation of drug dosages (Figure 9). This finding indicated that these THC compounds can break the balance of redox systems of pathogens and subsequently induce the increment of ROS, eventually endowing the tested bacteria with distinct apoptotic behaviors.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
“…ROS are the major mediators of fungal apoptosis, causing cell death by oxidizing biological macromolecules ( 25 ). Early studies showed that the attack on mitochondria by ROS overproduction could inhibit the mitochondrial respiratory function, leading to fungal cell death ( 26 28 ). Those reports coincide with our results, which showed that the level of ROS in S. globosa was significantly increased after laser treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our previous study, as a burst of ROS appears 3 hr after carabrone treatment of the hyphae. At the same time, the activity of antioxidant enzymes is inhibited and gene expression is increased (Wang et al ., 2019). The activity of peroxidase in the ∆GtCytc 1 , ∆GtCytb, ∆GtIsp, and 24‐HN‐1 mutants was significantly increased (71%, 58%, 65%, and 94%, respectively) compared with the wild‐type strain (Figure 5b), which is consistent with earlier reports suggesting that the activity of peroxidase is significantly activated when organisms are subjected to biotic or abiotic stresses (Allen, 1995; Meloni et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%